De l’individu au politique. L’angoisse comme régime d’expérience - Annabelle Allouch; Christelle Rabier; Clémentine Vidal-Naquet (Tracés, 2020)
While anxiety as a category is often used to designate a bodily sensation of discomfort peculiar to the individual, this issue of Tracés proposes to look at anxiety as a regime of experience in the face of uncertainty, no longer using the tools of psychoanalysis but those of the human and social sciences. The articles in the issue thus address the logics underlying the modes of manifestation of anxiety, taking into account their dimensions, which are at once corporeal, discursive and aesthetic, in original articles, an interview and a graphic work. The editorial returns in particular to the question of the socially situated nature of the expression of anguish, depending both on an institutional context and individual dispositions, but also their gendered aspect. However, analysing the manifestations of anxiety implies first of all questioning the conditions of its objectivation in medical discourse but also by the human and social sciences in all their diversity. If psychoanalytical discourse has imposed itself throughout the 20th century as the main vector for thinking of anguish as ontological and in this respect fundamentally different from fear (which is always linked to an object), the contribution of existentialist philosophy (Kierkegaard, in particular) allows us to think of anguish as man’s experimentation with the infinity of possibilities. As a learned category, anguish is also an ordinary category designating an emotion that can be considered as founding as much of a social group as of political modes of action. While anguish tends to be reduced to a process specific to the subject, the bias of our issue has therefore been to rethink this emotion in the light of the collective, that is to say, to make it the sign of a shared emotional regime in a given space and at a given time. If “experiencing anguish” comes out more from the body and the incorporated, to call oneself anguished would be to benefit from categories of understanding of the social world, notably those coming from psychoanalysis, which contribute not only to qualify its relationship to the world as pathological, but rather to affirm in the public space (after the private space) the legitimacy of the tortuous and painful singularity of this relationship.